Description of Staphylococcal Strains from Straw-Coloured Fruit Bat (Eidolon helvum) and Diamond Firetail (Stagonopleura guttata) and a Review of their Phylogenetic Relationships to Other Staphylococci - Monecke, Stefan; Schaumburg, Frieder; Shittu, Adebayo O.; Schwarz, Stefan; Mühldorfer, Kristin; Brandt, Christian; Braun, Sascha D.; Collatz, Maximilian; Diezel, Celia; Gawlik, Darius; Hanke, Dennis; Hotzel, Helmut; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The phylogenetic tree of the Staphylococcus aureus complex consists of several distinct clades and the majority of human and veterinary S. aureus isolates form one large clade. In addition, two divergent clades have recently been described as separate species. One was named Staphylococcus argenteus, due to the lack of the “golden” pigment staphyloxanthin. The second one is S. schweitzeri, found in humans and animals from Central and West Africa. In late 2021, two additional species, S. roterodami and S. singaporensis, have been described from clinical samples from Southeast Asia. In the present study, isolates and their genome sequences from wild Straw-coloured fruit bats (Eidolon helvum) and a Diamond firetail (Stagonopleura guttata, an estrildid finch) kept in a German aviary are described. The isolates possessed staphyloxanthin genes and were closer related to S. argenteus and S. schweitzeri than to S. aureus. Phylogenetic analysis revealed that they were nearly identical to both, S. roterodami and S. singaporensis. We propose considering the study isolates, the recently described S. roterodami and S. singaporensis as well as some Chinese strains with MLST profiles stored in the PubMLST database as different clonal complexes within one new species. According to the principle of priority we propose it should be named S. roterodami. This species is more widespread than previously believed, being observed in West Africa, Southeast Asia and Southern China. It has a zoonotic connection to bats and has been shown to be capable of causing skin and soft tissue infections in humans. It is positive for staphyloxanthin, and it could be mis-identified as S. aureus (or S. argenteus) using routine procedures. However, it can be identified based on distinct MLST alleles, and “S. aureus” sequence types ST2470, ST3135, ST3952, ST3960, ST3961, ST3963, ST3965, ST3980, ST4014, ST4075, ST4076, ST4185, ST4326, ST4569, ST6105, ST6106, ST6107, ST6108, ST6109, ST6999 and ST7342 belong to this species.